Conjunctival infiltrates and cytokines in an experimental immune-mediated blepharoconjunctivitis rat model - Hou, Aihua; Tin, Min Qi; Fenner, Beau; Liu, Yu-Chi; Tong, Louis (Frontiers in Medicine, 2023)
Purpose To characterize the histopathological and immunological findings of a rat model of allergic blepharoconjunctivitis (BC) and demonstrate its potential utility for the assessment of BC therapies. Methods Sprague-Dawley (SD) rats were immunized with ovalbumin (OVA) and topically challenged with OVA (BC group) or PBS (control group), while a corticosteroid group was pre-treated with triamcinolone acetate 24 hours before challenge. Morphological features were evaluated and tissues harvested for histological, flow cytometry and cytokine analysis. Results BC group rats developed eyelid excoriations, redness and conjunctival edema 24 hours after OVA challenge, while corticosteroid pre-treated and PBS challenged rats were unaffected. The BC features were reduced despite repeated challenges for 5 days. Massive immune cell infiltration was observed in conjunctivae of BC rats, while no significant infiltration was seen in the other groups. Populations of T cells, mono-macrophages, neutrophils and NK cells made up more than 77% of CD45+7AAD- cells in the conjunctival tissues. T cell proportions were increased at 96hr compared to 24hr post-challenge, while macrophages decreased during the same time period. Eosinophils and intraepithelial neutrophils were detected in BC rats, but not in the PBS and corticosteroid groups. BC eyes had significantly higher levels of IFN- and IL-2, while IL-4 and IL-6 levels were similar to controls. Conclusions A robust BC response was detected in this rat model which was suppressed by corticosteroid pre-treatment. Immune cell composition and cytokine profiles changed over time.